Complete Heart Block: A Rare Complication of Takotsubo Syndrome - Sakul, N. F. N. (Case Rep Cardiol, 2019)
Takotsubo syndrome was believed to be a rare acute cardiac event until recently with takotsubo cardiomyopathy being its most commonly recognized and often the diagnostic feature. Its diagnosis is becoming increasingly common with varied clinical manifestations most of whom have favorable clinical outcomes, yet it can be associated with life-threatening complications. We report a case of takotsubo syndrome leading to complete heart block which is a unique complication of an otherwise self-resolving disease.